Dynamics of the Edgeworth-Kuiper Belt beyond 50 AU : Spread of a primordial thin disk - Brunini, Adrián (2002)
In this paper we report numerical simulations of the dynamical evolution of the region a > 50 AU. We found that some dynamical effects such as high-order secular resonances with the rate of precession of Neptune's node of the form kΩ· − Ω·Nep with k = 4,5, ... or combined mean motion resonances with Uranus and Neptune of the form knN + jnU + mn ∼ 0 may increase the area of a very thin primordial disk in this region by a factor of up to 2 after 4.5 Gy of evolution.